Pengaruh Kecerdasan Emosional dan Organizational Citizenship Behavior (OCB) terhadap Kinerja Peternak Ayam Ras Pedaging: The Effect of Emotional Intelligence and Organizational Citizenship Behavior (OCB) on the Performance of Broiler Breeders - Ariesta, Iche (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2016)
One line of business in the livestock sector is very dynamic development of agribusiness broiler breeding with a partnership plasma core. Development of agribusiness broiler farm will be successful if farmers are able to manage the cattle business well through improved individual performance to the fullest which is characterized by an individual’s ability to control and manage emotions and behave voluntarily without any coercion by contract organizations. This study aims to determine how much influence the emotional intelligence and Organizational Citizenship Behavior (OCB) on the performance of broiler breeders. This study uses a quantitative approach with a correlation method. The selected study site is CV Amerta Farm Corp Probolinggo, because it is one of agribusiness broiler farms that implement core-plasma partnership pattern. The number of respondents in this study amounted to 69 people. Independent variables in this study are emotional intelligence and Organizational Citizenship Behavior (OCB), while the dependent variable is the performance of broiler breeders. Data analysis techniques used in this study is a Structural Equation Modeling (SEM) with the Partial Least Square (PLS) technique assisted with SmartPLS 2.0 application program.